ALL-OPTICAL LOGIC GATE OPERATION WITH A MULTI-CORE NONLINEAR PHOTONIC CRYSTAL FIBER - Dang Quang Huy, Nguyen; Phuong Yen, Tran; Duc Tho, Do; Xuan Thang, Cao; Duc Tinh, Bui; Ky Vi, Tran; Longobucco, Mattia; Thi Dung, Nguyen; Thi Hai, Tran; Viet Hung, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2024)
In this paper, we propose the design of a photonic crystal fiber with four central cores infiltrated by a high-index liquid to achieve highly efficient control of light guidance. We analyze the field distribution, effective mode area, and dispersion characteristics of the fundamental guided modes of the fiber. Within the coupled-mode theory, the pulse propagation in the fiber is governed by coupled nonlinear Schrödinger equations. We use the split-step Fourier method to simulate the propagation of pulses numerically. The results show three features of the dynamics: oscillation, switching, and self-trapping. We predict that the fiber could operate as a logic-gate device by introducing suitable input and control signals.